Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12882-020-01753-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a pedometer-based walking intervention on body composition in patients with ESRD: a randomized controlled trial

Abstract: Background: A randomized trial of a pedometer-based intervention with weekly activity goals led to a modest increase in step count among dialysis patients. In a secondary analysis, we investigated the effect of this intervention on body composition.Methods: Sixty dialysis patients were randomized to standard care or a 6-month program consisting of 3 months of pedometers and weekly step count targets and 3 months of post-intervention follow-up. We obtained bioelectrical impedance spectroscopy (BIS) data on 54 o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
1
8
0
2
Order By: Relevance
“…This study reported a decrease in fat percentage of 3.52% (equivalent to 3.01 kg), a decrease in visceral fat percentage of 1.29% (equivalent to 0.95 kg), and a decrease in waist circumference of 2.91 cm. These findings are supported by other studies that showed a range of body fat loss from 1.9% to 3.9% after 12-week and 24-week pedometer-based interventions [ 21 , 23 , 32 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study reported a decrease in fat percentage of 3.52% (equivalent to 3.01 kg), a decrease in visceral fat percentage of 1.29% (equivalent to 0.95 kg), and a decrease in waist circumference of 2.91 cm. These findings are supported by other studies that showed a range of body fat loss from 1.9% to 3.9% after 12-week and 24-week pedometer-based interventions [ 21 , 23 , 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Two studies were conducted on middle-aged and older adults, using pedometer-based interventions over a period of 12 weeks. Those studies found that 12-week interventions produced significant decreases in body weight (ranging from 1.2 to 2.5 kg) and BMI (ranging from 0.6 to 1.0 kg/m 2 , p <0.001) [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esto se debe a que proporcionan una retroalimentación inmediata al usuario, al visualizar el número de pasos dados en el día, permitiendo el cumplimiento de objetivos individuales para estimularlos a alcanzar un mayor número de pasos 19 . Eso demuestra que pueden generar beneficios en la composición corporal y otros parámetros que contribuyen a la salud cardiovascular 13 .…”
Section: Desarrollounclassified
“…Al ser un instrumento práctico y accesible para la población en general, el podómetro cuantifica el número de pasos y es usado para realizar programas de intervención basados en caminata 12 , ya que resulta efectivo al brindar motivación e incrementar la actividad física en personas con alguna morbilidad crónica y así beneficiar su salud 13 .…”
Section: Introductionunclassified
“…Although aerobic exercise has been shown to increase aerobic capacity in CHD patients [ 42 ], resistance-type exercise is considered to be the most potent form of physical activity to increase muscle mass and strength [ 43 ]. Nevertheless, a recent study by Sheshadri et al [ 44 ▪ ] reported that low-intensity exercise (i.e. walking) already resulted in improved muscle mass maintenance in CHD patients.…”
Section: Physical Activity To Augment Post-prandial Muscle Protein Symentioning
confidence: 99%